$y' - \frac{1}{t}y = y^2 - \frac{3}{t^2}, y_p = \frac{1}{t}$

Method 1

To obtain a Bernoulli ODE, we plug $y = \frac{1}{t} + u$ into the Riccati ODE, yielding $u' - \frac{3}{t}u = u^2$. To obtain a linear ODE, we plug $u = \frac{1}{v}$ into the Bernoulli ODE, yielding $v' + \frac{3}{t}v = -1$.

Thus, $v = \frac{C - t^4}{4t^3}$, which entails that $u = \frac{4t^3}{C - t^4}$, which entails that $y = \frac{3t^4 + C}{Ct - t^5}$.

Method 2

To obtain a second-order linear ODE, we plug $y = -\frac{w'}{w}$ into the Riccati ODE, yielding $w'' - \frac{1}{t}w' - \frac{3}{t^2}w = 0$. Since our particular solution $\frac{1}{t}$ also solves this homogeneous equation, we can use reduction of order to find that $w = \frac{At^4 +B}{t}$. It is interesting to note that the first-order linear ODE found through reduction of order is $x' - \frac{3}{t}x = 0$, which is similar but not identical to the first-order linear ODE in $v$ found through Method 1. Plugging $w = \frac{At^4 +B}{t}$ into $y = -\frac{w'}{w}$ yields the solution $y = \frac{B - 3At^4}{At^5 + Bt}$.

These two solutions match iff $A = -1$, but we wouldn't have known that if we'd only used Method 2 to solve the Riccati ODE. I tried plugging $y = \frac{B - 3At^4}{At^5 + Bt}$ into the Riccati ODE to fish for the fact that $A = -1$, but instead I got $B = 0$, which isn't even generally true. Why does $B = 0$ come out of this process, and if we solved the ODE with Method 2, how could we have discovered that $A = -1$ without doing the problem a second time using Method 1.

  • $\begingroup$ You could also just cancel and set $C=-B/A$. So if you got $B=0$ you made some error while inserting. $\endgroup$ – LutzL Oct 9 at 17:17

Both of your approaches are correctly carried out. You get more generally the first form from the second for $A\ne 0$ by canceling $-A$ in the quotient and setting $C=-\frac BA$.

To the second approach one could remark that the equation you get is of the Euler-Cauchy type so that you do not even need the provided solution, you get the basis solutions $t^m$ from the characteristic polynomial $0=m(m-1)-m-3=(m+1)(m-3)$, so that $w=At^3+Bt^{-1}$.

  • $\begingroup$ Is there any way I could have known to divide by $-A$ instead of, say, $B$ or $-B$ (and then set $C = \frac{A}{B}$ or $C = -\frac{B}{A}$ without going through Method 1? $\endgroup$ – user10478 Oct 11 at 3:11
  • 1
    $\begingroup$ No. These other variants, and even with the two constants, are all valid general solution formulas. Note that if you reduce to one constant, you will lose a valid solution, $t^{-1}$ or $-3t^{-1}$. $\endgroup$ – LutzL Oct 11 at 6:01

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.